Tectonics and sedimentation in the Curitiba Basin, south of Brazil - Salamuni, E.; Ebert, H. D.; Borges, M. D.; Hasui, Y.; Costa, JBS; Salamuni, R. (Elsevier B.V., 2003)
The Curitiba Basin, Parana, lies parallel to the west side of the Serra do Mar range and is part of a continental rift near the Atlantic coast of southeastern Brazil. It bears unconsolidated and poorly consolidated sediments divided in two formations: the lower Guabirotuba Formation and the overlying Tinguis Formation, both developed over Precambrian basement. Field observations, water well drill cores, and interpretations of satellite images lead to the inference that regional tectonic processes were responsible for the origin of the Basin in the continental rift context and for morphotecatonic evolution through block tilting, dissection, and erosion. The structural framework of the sediments and the basement is characterized by NE-SW-trending normal faults (extensional tectonic D-1 event) reactivated by NE-SW-trending strike-slip and reverse oblique faults (younger transtensional tectonic D-2' to transpressional tectonic D-2, event). This tectonic event, which started in the Paleogene and controlled the basin geometry, began as a halfgraben and was later reactivated as a pull-apart basin. D-2 is a neotectonic event that controls the current morphostructures. The Basin is connected to the structural rearrangement of the South American platform, which underwent a generalized extensional or trantensional process and, in late Oligocene, changed to a compressional to transpressional regime. (C) 2003 Elsevier B.V. Ltd. All rights reserved.
Keywords: sedimentary basin; Tertiary and Quaternary tectonics; morphotectonics; neotectonics